Study on Chemical Composition of Cassava Root Ferment with Yeast (Saccharomyces cerevisiae) And Urea - manivanh, nouphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to investigate the chemical composition of cassava root fermented with yeast (Saccharomyces cerevisiae) and urea in order to enhance their nutritional value for use in animal feed. The experiment was arranged in a 2 × 3 × 4 factorial design under a Completely Randomized Design (CRD), consisting of six treatments with four replications per treatment. The experiment was conducted in the laboratory of the Department of Animal Science, Faculty of Agriculture and Forest Resources, Souphanouvong University. Data were collected at 0, 3, 7, and 14 days of fermentation. The results of the study indicated that fermentation with yeast and urea significantly affected the chemical composition of cassava root. The percentages of dry matter (DM) and organic matter (OM) in both steamed and non-steamed fermented cassava were significantly different (P < 0.05) on day 0; However, no significant differences were observed on days 3, 7, and 14 (P > 0.05). Crude protein (CP) showed no significant difference at the initial stage of fermentation, but a significant difference was observed on day 7 (P < 0.05). Importantly, true protein (TP) tended to increase with increasing levels of urea supplementation (0, 1, and 2%) and fermentation time. The TP content increased significantly (P < 0.05) from 2.7% to 7.3% by day 14. In conclusion, fermenting cassava tubers with yeast in combination with appropriate levels of urea can significantly increase the true protein (TP) content, thereby enhancing the nutritional value of cassava as a feed ingredient for animal production.